Prevalence of anxiety, depression, and stress among parents of neonates admitted to neonatal intensive care unit: a systematic review and meta-analysis - Asha P. Shetty; Kurvatteppa Halemani; Alwin Issac; Latha Thimmappa; Sanjay Dhiraaj; Radha K; Prabhaker Mishra; Vijai Datta Upadhyaya (The Korean Pediatric Society, 2024)
Background Neonatal intensive care unit (NICU) admission causes significant distress that can hinder the successful transition into parenthood, child-parent relations, and child development. Purpose This systematic review and meta-analysis aimed to understand parental psychological phenomena. Here we assessed the emotional response of parents of newborns during NICU admission. Methods Two authors independently searched the PubMed, Cumulative Index to Nursing and Allied Health Literature, Embase, Clinical Key, and Google Scholar databases for studies published between January 01, 2004, and December 31, 2021. The review followed Cochrane collaboration guidelines and the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) statement. The quality of the included studies was assessed using the modified Newcastle-Ottawa Scale. Stata software (version 16) was used to compute the results. Results This review comprised 6,822 parents (5,083 mothers, 1,788 fathers; age range, 18-37 years) of NICU patients. The gestational ages and neonatal weights were 25.5-42 weeks and 750-2,920 g, respectively. The pooled prevalence of anxiety was higher among mothers (effect size [ES], 0.51; 95% confidence interval [CI], 0.41-0.61; and heterogeneity [I2]=97.1%; P<0.001) than among fathers (ES, 0.26; 95% CI, 0.11-0.42; I2=96.6%; P<0.001). Further, the pooled prevalence of depression was higher among mothers (ES, 0.31; 95% CI, 0.24-0.38; I2=91.5%; P<0.001) than among fathers (ES, 0.12; 95% CI, 0.03-0.22; I2=85.6%; P<0.001). Similarly, the pooled prevalence of stress was higher among mothers (ES, 0.41; 95% CI, 0.31-0.51; I2= 93.9%; P<0.001) than among fathers (ES, 0.22; 95% CI, 0.09-0.34; I2=85.2%; P<0.001). Conclusion NICU admission is more stressful for mothers than fathers and can affect mental health and quality of life. Mothers reported a higher pooled prevalence of stress, anxiety, and depression than fathers, possibly attributable to their feelings about birthing a sick child.